2021
DOI: 10.2337/figshare.15108567.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical Role for Hepatocyte-Specific eNOS in NAFLD and NASH

Abstract: Regulation of endothelial nitric oxide synthase (eNOS) in hepatocytes may be an important target in nonalcoholic fatty liver disease (NAFLD) development and progression to steatohepatitis (NASH). In this study, we show genetic deletion and viral knockdown of hepatocyte-specific eNOS exacerbated hepatic steatosis and inflammation, decreased hepatic mitochondrial fatty acid oxidation and respiration, increased mitochondrial H<sub>2</sub>O<sub>2</sub> emission, and impaired the hepatic mit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 0 publications
6
14
0
Order By: Relevance
“…Previous reports have shown that exercise attenuates NAFLD/NASH‐induced elevated oxidative stress in rodents (24,25). As seen here and shown previously by our group (14), hepatic mitochondrial H 2 O 2 emission in eNOS hep−/− mice was ~50% higher compared with eNOS fl/fl mice (Figure 3). This effect was completely abrogated with exercise, accompanied by induction of several genes involved in mitigating H 2 O 2 production ( arg1 , cat , and gpx1 ), indicating that eNOS in hepatocytes does not appear to be required for the exercise‐induced reduction of ROS emission or antioxidant defense in the liver.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Previous reports have shown that exercise attenuates NAFLD/NASH‐induced elevated oxidative stress in rodents (24,25). As seen here and shown previously by our group (14), hepatic mitochondrial H 2 O 2 emission in eNOS hep−/− mice was ~50% higher compared with eNOS fl/fl mice (Figure 3). This effect was completely abrogated with exercise, accompanied by induction of several genes involved in mitigating H 2 O 2 production ( arg1 , cat , and gpx1 ), indicating that eNOS in hepatocytes does not appear to be required for the exercise‐induced reduction of ROS emission or antioxidant defense in the liver.…”
Section: Discussionsupporting
confidence: 90%
“…It is unclear whether the blunted responses to exercise are mediated by lack of eNOS‐derived nitric oxide (NO). We recently reported that there is no compensatory upregulation of hepatic iNOS or nNOS expression in eNOS hep−/− mice, nor is eNOS expression altered in other tissues that we assessed in eNOS hep−/− mice (14). However, we did report that hepatocytes from eNOS hep−/− mice tend to have a slight reduction in nitrate/nitrite levels, a surrogate measure of NO (14).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations